IL-4Rα signalling in B cells and T cells play differential roles in acute and chronic atopic dermatitis - Martyna Scibiorek; Nontobeko Mthembu; Sandisiwe Mangali; Amkele Ngomti; Paul Ikwegbue; Frank Brombacher; Sabelo Hadebe (Scientific Reports, 2023)
Abstract Atopic dermatitis (AD) is a common pruritic inflammatory skin disease with complex environmental and genetic predisposing factors. Primary skin barrier dysfunction and aberrant T helper 2 (TH2) responses to common allergens, together with increased serum IgE antibodies, characterise the disease. B and T cells are essential in the disease manifestation, however, the exact mechanism of how these cells is involved is unclear. Targeting interleukin 4 receptor alpha (IL-4Rα), an IL-4/IL-13 signalling axis, with dupilumab shows efficacy in AD. We investigated the importance of IL-4Rα signalling specifically on B and T cells during acute and chronic models of AD. We used House dust mite (HDM) and Ovalbumin (OVA) in chronic models and a low-calcemic analog of vitamin D (MC903) for acute models of AD. We used mb1creIL-4Rα−/lox, iLCKcreIL-4Rα−/lox, LCKcreIL-4Rα−/lox, CD4creIL-4Rα−/lox, Foxp3creIL-4Rα−/lox and IL-4Rα−/lox littermate controls. IL-4Rα-responsive B cells were essential in serum IgE levels, but not in epidermal thickening in both chronic and acute models. IL-4Rα-responsive T cells were essential in epidermal thickening in the pan-T cell, but not CD4 or CD8 T cells suggesting the importance of γδT cells during acute AD. Our results suggest that IL-4Rα responsiveness on innate T cells regulates acute atopic dermatitis, while on B cells it regulates IgE.